The Influence of the Physicochemical Parameters on the Ortho Phosphate and Total Phosphate Concentrations of Maninjau Lake. (September 2020) - Komala, P S; Primasari, B; Ayunin, Q
Abstract: The study was conducted in order to examine the relationship between the physicochemical parameters (temperature, DO and pH) with the orthophosphate (OP) and total phosphate (TP) concentrations based on the depth of Maninjau Lake. Samples were taken at the center of the lake near to a domestic area, endemic fisheries and a hydropower site. The OP concentration ranged from 0.182 - 0.570 mg/L and the TP of 0.265 - 0.603 mg/L indicated that Maninjau Lake was hypertrophic. This does not meet the quality standards regulated by the Indonesian Government. The physicochemical parameters of temperature, pH, and DO have a strong negative correlation with OP and TP concentrations with a correlation value of 0.828-0.982. ANOVA showed that depth stratification affects the OP and TP concentrations while the variation of sampling time does not affect the concentrations. The highest total phosphate concentration value was at the aquaculture cage location which exceeded the second class quality standard based on Government Regulation No. 82 of 2001. It shows that the aquaculture activities result in excess phosphate loads that can trigger lake eutrophication.